Manajemen Pengelolaan Warung Makan Di Wisata Waduk Gajah Mungkur Dalam Peningkatan Kesejahteraan Masyarakat Desa Sendang Kecamatan Wonogiri Kabupaten Wonogiri - Sugiyanto Sugiyanto (Lisyabab : Jurnal Studi Islam dan Sosial, 2020)
This study aims to analyze the business management of the entrepreneurs of food stalls in the Tourism Object of Gajah Mungkur Wonogiri Reservoir in relation to improving their welfare. The results of the research analysis are as follows: (1) The entrepreneurs of the food stalls generally give a positive response to the research conducted because with this research they gain knowledge about the procedures or management of business management so that they are able to apply in running the businesses they manage. (2) From 10 respondents, there were 8 respondents who had used business management well in managing their food stall business. Although it is still a simple pattern of management that they apply, but with this management they are able to manage their stalls well so that their business develops. And their business can survive until now even though the operating profit obtained is not yet maximal but able to support the family economy. (3) respondents of their businesses have not been able to develop because they are still weak in business management. The management they have implemented has not been able to be carried out to the fullest. They easily spend or spend money from operating income without considering that the money is venture capital money that should be played back in the business. So that the food stalls they manage are getting more and more receding.